ANALYSIS OF THE PSYCHO-EMOTIONAL STATE OF UKRAINIANS AND ASPECTS OF PSYCHOLOGICAL ASSISTANCE AT THE BEGINNING OF THE CURRENT WAR - Osadchenko , Inna; Perepeliuk , Tetiana; Olkhovetsky , Sergey (Psychological Prospects Journal, 2023)
Purpose. This study aims to characterize the psychoemotional states of Ukrainians and aspects of providing psychological assistance at the beginning of the current war, the first two months, based on the analysis of scientific sources, statistical data, and the results of empirical research.Methods. To achieve this aim, we used the following research methods: generalized and comparative-systemic analysis of scientific sources, systematization and modelling of research results, comprehensive analysis of the experience of psychologists working within volunteer projects, concealed population surveys based on the Raven questionnaire (Raven, 1997), methods of mathematical statistics, statistical analysis of data from the Telegram channel «SvitloPodiya», analysis of private and publicly available posts in online event chats and social networks, the use of standardized questionnaires and narrative writing, as well as the design of a cross-sectional study. We used Statistica 12 software and the Linguistic Inquiry and Word Count (LIWC-2015) software for statistical analysis.Results. The study revealed that factors influencing the deterioration of the psychoemotional state of Ukrainians included job loss or the inability to attend work or school, increased free time due to inactivity, loneliness, insufficient information about behaviour rules during bombardments, alarm signals and shelter, a low culture of seeking help from psychologists, parents' inability to explain the war situation to children. Typical negative characteristics of the population's psychoemotional state at the beginning of the war in Ukraine were latent depression, mass anger, various types of fear, egoism, maximum self-concern, a demonstrative need for attention through hysterics and panic attacks, and more.Conclusions. Improvements in the psychoemotional state of the population were facilitated by measures including structured and active work, especially volunteer work, positive messages and video recommendations via social media, positive text messages every morning, guidance on social media for self-regulation and emotional management, the efforts of volunteer Telegram channels and other programs for volunteer psychological support, as well as specially designed psycho-pedagogical sessions for children of different ages.  Especially designed are online classes for students, daily supervision by educators and psychologists, the application of a psycho-pedagogical approach in education, the dissemination of psycho-pedagogical recommendations to educators, psychologists, and parents, and hosting accompanying webinars, online and in-person training sessions on identifying and addressing symptoms of anxiety disorders and panic attacks, and stabilising the psychoemotional state of individuals of all ages, among other initiatives. The importance of modernising and promoting the effectiveness of social and psychological services in Ukraine is emphasised. It is recommended that self-regulation skills for regulating psychoemotional states be taught from preschool age and introduced to compulsory classes in both general and higher education institutions.
Keywords: psychoemotional state; war; emotions; feelings; resilience; psychopedagogical assistance; psychological support; psychological assistance